Diversification versus specialization in scientific research: Which strategy pays off?. (April 2019) - Abramo, Giovanni; D'Angelo, Ciriaco Andrea; Di Costa, Flavia
Abstract: The current work addresses a theme previously unexplored in the literature: that of whether the results arising from research activity in fields other than the scientist's primary field have greater value than the others. Operationally, the authors proceed by identifying: the scientific production of each researcher under observation; field classification of the publications; the field containing the greatest number of the researcher's publications; attribution of value of each publication. The results show that diversification at the aggregate level does not pay off, although there are some exceptions at the level of individual disciplines. The implications at policy level are notable. Since the incentive systems of research organizations are based on the impact of scientific output, the scientists concerned could resist engaging in multidisciplinary projects. Highlights: We test whether specialized publications have greater impact than diversified ones. The term "Specialized" refers to publications in the field with the greatest number of the researcher's papers. Results show that diversification at the aggregate level does not pay off, with some exceptions in individual disciplines. The implications at policy level are notable.